Atomoxetine in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder. Systematic Review of Review Papers 2009-2011. An Update for Clinicians - Chris J. Bushe Mbbs; Nicola Savill (Journal of Central Nervous System Disease, 2011)
Attention deficit/hyperactivity disorder (ADHD) is a common disorder and a plethora of new data has been published from clinical trials and national epidemiological databases in the last three years. In the United Kingdom Atomoxetine is currently the only licensed non-stimulant medication. As part of a systematic review of atomoxetine data Jan 2009-June 2011 formal searches found 750 citations. From these 13 met criteria for either review or systematic review papers and contained clinical data synthesis on atomoxetine. No individual review paper alone would be sufficient for clinicians to be updated at that time on all clinical aspects of atomoxetine data. The crucial data relating to clinical parity of atomoxetine and methylphenidate in trials and meta-analysis where relevant confounding biases are removed are not often discussed. Systematic review of complex data is critical for ADHD clinicians and will need regular updating due to the large volume of new data.